2022
DOI: 10.3389/fneur.2022.850429
|View full text |Cite
|
Sign up to set email alerts
|

Clot Meniscus Sign Is Associated With Thrombus Permeability and Choice of Mechanical Thrombectomy Technique in Acute Middle Cerebral Artery Occlusion

Abstract: Background and PurposeThe method of mechanical thrombectomy (MT) is related to vascular anatomy and stroke etiology. Meniscus sign and thrombus permeability as imaging markers may be instructive for the selection of MT. This study aims to clarify the relationship among meniscus sign, thrombus permeability, and choice of MT in patients with acute middle cerebral artery occlusion.Materials and MethodsA total of 111 patients with acute middle cerebral artery occlusion (MCAO) who underwent MT were retrospectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…A possible link supporting this hypothesis is that thrombi with cardioembolic origin, usually rich in fibrin and platelets, also have an increased perviousness in computed tomography [21], which is known to be associated with higher success of intravenous thrombolysis [22]. Although, in our study, the meniscus sign was more frequent in patients with cardioembolic stroke etiology, studies report conflicting results in what the association between meniscus sign and thrombus perviousness is concerned [8,23].…”
supporting
confidence: 49%
See 1 more Smart Citation
“…A possible link supporting this hypothesis is that thrombi with cardioembolic origin, usually rich in fibrin and platelets, also have an increased perviousness in computed tomography [21], which is known to be associated with higher success of intravenous thrombolysis [22]. Although, in our study, the meniscus sign was more frequent in patients with cardioembolic stroke etiology, studies report conflicting results in what the association between meniscus sign and thrombus perviousness is concerned [8,23].…”
supporting
confidence: 49%
“…Successful reperfusion was, however, not different between the two different primary techniques and clinical outcomes were similar. A recent study of patients with M1 and M2 occlusions showed better complete recanalization rates and better functional outcomes in patients with meniscus sign who had been treated with contact aspiration in comparison to stent-retriever [23]. Although contact aspiration technique in patients with meniscus sign was independently associated with complete recanalization, the analysis for the prediction of outcome was not adjusted for relevant co-variates in this study.…”
mentioning
confidence: 58%
“…It has been postulated that clots with a meniscus sign may be rich in red blood cells and break down easily compared to a fibrin clot. Supporting this are studies which identified a higher recanalization rate and better functional outcomes in patients who received direct aspiration as opposed to stent retriever for LVO AIS presenting with a meniscus sign (10). However, a more recent multicentric study involving prospective local registries of high-volume centres subsequently demonstrated little prognostic significance for the meniscus sign, consistent with what was found in our center (26).…”
Section: Discussionsupporting
confidence: 85%
“…For example, poor baseline collateral flow status and Alberta Stroke Program Early CT Score (ASPECTS), assessed via CT angiography, are associated with a larger ischemic core and worse functional outcomes (5,6). Other radiological variables which have been investigated include clot characteristics including clot length, density, surface phenotype, truncal versus branch-type occlusions and the presence of a meniscus sign (7)(8)(9)(10)(11). Further radiological variables that have been studied pertain to vascular anatomy and include parameters that quantify vascular tortuosity such as the aortic arch type (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…For example, poor baseline collateral flow status and Alberta Stroke Program Early CT Score (ASPECTS), assessed via CT angiography, are associated with a larger ischemic core and worse functional outcomes (5,6). Other radiological variables which have been investigated include clot characteristics including clot length, density, surface phenotype, truncal versus branch-type occlusions and the presence of a meniscus sign (7)(8)(9)(10)(11). Further radiological variables that have been studied pertain to vascular anatomy and include parameters that quantify vascular tortuosity such as the aortic arch type (12,13).…”
Section: Introductionmentioning
confidence: 99%